2002
DOI: 10.1038/nm744
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow–derived stem cells target retinal astrocytes and can promote or inhibit retinal angiogenesis

Abstract: Adult bone marrow (BM) contains cells capable of differentiating along hematopoietic (Lin(+)) or non-hematopoietic (Lin(-)) lineages. Lin(-) hematopoietic stem cells (HSCs) have recently been shown to contain a population of endothelial precursor cells (EPCs) capable of forming blood vessels. Here we show that intravitreally injected Lin(-) BM cells selectively target retinal astrocytes, cells that serve as a template for both developmental and injury-associated retinal angiogenesis. When Lin(-) BM cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
230
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(244 citation statements)
references
References 21 publications
5
230
1
2
Order By: Relevance
“…Studies in a model of ischemic retinopathy have shown that bone marrow-derived hematopoietic stem cells participate in retinal neovascularization (Grant et al, 2002). Investigations using cell-based gene therapy in the mouse OIR model showed that these cells can rescue and stabilize degenerating vessels, and the cells can inhibit new vessel formation in a mouse model of retinal degeneration (Otani et al, 2002). By contrast, studies using animal models for ocular vascular damage, including diabetes, ischemia/reperfusion injury and OIR, have shown that cells from normal donors attach and assimilate into the existing vasculature.…”
Section: Vegf and Retinalmentioning
confidence: 99%
“…Studies in a model of ischemic retinopathy have shown that bone marrow-derived hematopoietic stem cells participate in retinal neovascularization (Grant et al, 2002). Investigations using cell-based gene therapy in the mouse OIR model showed that these cells can rescue and stabilize degenerating vessels, and the cells can inhibit new vessel formation in a mouse model of retinal degeneration (Otani et al, 2002). By contrast, studies using animal models for ocular vascular damage, including diabetes, ischemia/reperfusion injury and OIR, have shown that cells from normal donors attach and assimilate into the existing vasculature.…”
Section: Vegf and Retinalmentioning
confidence: 99%
“…For stem cells with endothelial potential, retinal revascularization can be observed directly through the pupil, making the retina a good model system for studying stem cell-mediated CNS revascularization in general. Restoration of vasculature located on the inner retinal surface by BMSCs is a rational approach toward rescue of retinal neurons lost in retinal vascular disorders, such as diabetic retinopathy [52][53][54]. Injection of BMSCs into the eye improves retinal circulation, enhances survival of outer retinal neurons, and rescues vision in both ischemic and nonischemic mouse models of retinal degeneration [53,55].…”
Section: Non-neural Stem Cellsmentioning
confidence: 99%
“…Although this approach showed a dramatic rescue effect, there was a limitation in that intravitreally injected bone marrow (BM)-derived stem cells were effectively incorporated into the retina only during an early, postnatal developmental stage, but not in adult mice. Directly injected exogenous Lin -HSCs only targeted activated astrocytes that are observed in neonatal mice or in an injury-induced model in the adult (20)(21)(22) .…”
Section: A) Cellular Differentiationmentioning
confidence: 99%